2007
DOI: 10.1103/physrevlett.98.057201
|View full text |Cite
|
Sign up to set email alerts
|

Will Spin-Relaxation Times in Molecular Magnets Permit Quantum Information Processing?

Abstract: Using X-band pulsed electron spin resonance, we report the intrinsic spin-lattice (T1) and phase coherence (T2) relaxation times in molecular nanomagnets for the first time. In Cr7M heterometallic wheels, with M = Ni and Mn, phase coherence relaxation is dominated by the coupling of the electron spin to protons within the molecule. In deuterated samples T2 reaches 3 µs at low temperatures, which is several orders of magnitude longer than the duration of spin manipulations, satisfying a prerequisite for the dep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
562
1
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 729 publications
(579 citation statements)
references
References 31 publications
10
562
1
6
Order By: Relevance
“…preserved full wave function, it is first at measurement (collapse of wave function) it is decided which particle will have α and which β. In all practical experiments there will be some surrounding matter (gas, liquid or solid state) that could cause admixture of singlet and triplet states: any external perturbation may thus give rise to a spin change, for example, via some spin-lattice kind of relaxation mechanism (Atkins et al 1973;Ardavan et al 2007). Here temperature, reflecting somehow the system's degree of excitation, and the fact that there is generally a radiation field present associated with a certain temperature, can be an important parameter (Ninham & Daicic, 1998;Wennerstrom et al 1999) -higher temperature observed to shorten the relaxation time.…”
Section: Distance and Time Dependence Of An Atomic Entangled Statementioning
confidence: 99%
“…preserved full wave function, it is first at measurement (collapse of wave function) it is decided which particle will have α and which β. In all practical experiments there will be some surrounding matter (gas, liquid or solid state) that could cause admixture of singlet and triplet states: any external perturbation may thus give rise to a spin change, for example, via some spin-lattice kind of relaxation mechanism (Atkins et al 1973;Ardavan et al 2007). Here temperature, reflecting somehow the system's degree of excitation, and the fact that there is generally a radiation field present associated with a certain temperature, can be an important parameter (Ninham & Daicic, 1998;Wennerstrom et al 1999) -higher temperature observed to shorten the relaxation time.…”
Section: Distance and Time Dependence Of An Atomic Entangled Statementioning
confidence: 99%
“…1 μs at 5 K2a). The spin echo of the more slowly relaxing spin is measured and the modulation of this echo caused by the spontaneous flipping of the more rapidly relaxing spin allows the spin⋅⋅⋅spin interaction to be quantified.…”
mentioning
confidence: 93%
“…The decoherence from the chemical control cannot be easily eliminated because of the permanent interactions with the surrounding [18]. Simultaneously, the most straightforward and conventional way is to adopt an external magnetic field produced by electron spin resonance pulses [7]. Although the decoherence of single molecular magnets can be suppressed by strong magnetic fields, it is preferable to apply electric fields that are controllable and suitable on very small spatial and temporal scales.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the exchange of energy and information between the system and the environment, the non-Markovian dynamics of quantum states always occur in the realistic experimental systems [3][4][5]. Recently, much attentions have been paid to the control of the decoherence of many-body quantum systems [6,7] such as spin clusters and single molecular magnets [8]. As a class of systems with rich quantum properties, single molecular magnets at low energies can serve as a large-spin system or a collection of interacting spins [9][10][11].…”
Section: Introductionmentioning
confidence: 99%